Mistreatment of Women in the Labour Rooms of India: A Call to Action - Durga A. Verneka; Sangeeta Rege (My University, 2020)
The bulletin highlights many hidden aspects of motherhood that have been very little studied and analyzed. It deliberates upon dehumanization of birth by highlighting the issues of physical and verbal abuse to women in labour, 'violence' in labour rooms, disrespect and abuse during child birth and there after.
MFC Bulletin
Keywords: Matherhood; Maternal Health; Violence in Labour rooms; Violence against women